Pengaruh Kompensasi Dan Motivasi Kerja Terhadap Kepuasan Karyawan Di Kantor Samsat Karawang - Syifa Edenia; Sungkono (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This research aims to evaluate the impact of compensation and work motivation on employee satisfaction at the Karawang Samsat Office. Compensation and work motivation are two crucial factors that can influence employee job satisfaction levels. The research method applied is a quantitative method with a survey approach. Data was collected through questionnaires distributed to employees at the Karawang Samsat Office. Data analysis was carried out using multiple linear regression techniques to identify the simultaneous and partial influence of the independent variables (compensation and work motivation) on the dependent variable (employee satisfaction). The research results show that compensation and work motivation have a significant influence on employee satisfaction, both simultaneously and partially. These findings imply that increasing compensation and work motivation can increase employee job satisfaction at the Karawang Samsat Office.